Yemen: Cholera outbreak and the ongoing armed conflict - Fekri Ali Dureab; Khalid Shibib; Reema Al-Yousufi; Albrecht Jahn (Journal of Infection in Developing Countries)
Yemen was affected by a major cholera epidemic in 2016, while a civil war, which has devastated the country since March 2015, has exacerbated the humanitarian situation. Cholera is a disease caused by the bacterium Vibrio cholera, thus this study aims to analyze the epidemiological features of the outbreak and explore the relation of the outbreak to the current armed conflict situation.